Electronic marketing and its effect on the quality of banking services: A field study on a sample of old commercial banks (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The research aims to know the quality of the banking service The extent to which the customer understands the importance of electronic marketing And the extent of sophistication in the provision of services by the Bank to customers Are customerssatisfied with the banking services provided? Through the provision of a questionnaire distributed to 60 customers They were selected in a simple random way and the search reached :1 .There is volatility in the quality of banking service2. Lack of awareness of the importance of e-marketing3.Banks need to keep pace with development through the need to provide an information base Which will help the Iraqi commercial banking departments.